Implementation inside Safeguarding Principles UNESCO Convention for the Safeguarding of the Intangible Cultural Heritage 2003 in Indonesia - Rania Sekar Dahayu; Khoirur Rizal Lutfi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The personality of a nation will be reflected through its culture. Culture is a form of intangible wealth owned by a country. Intangible Cultural Heritage is the cultural heritage of the ancestors that is passed down to the next generation. Intangible Cultural Heritage has cultural, political and economic values. Intangible Property Inheritance has been regulated in the 2003 UNESCO Convention which “Protection” referred to the word "safeguarding". The purpose of this is to discuss the concept of "Safeguarding" according to the 2003 UNESCO Convention for The Safeguarding of the Intagible Cultural Heritage and examine its application in Indonesia. The method of the study is a normative juridical legal research with a statute and a case approach. Meanwhile, the efforts made by the government include making intellectual property rights, making catalog with a list of Indonesia’s intangible heritage and create communities that are interested in various forms of heritage and Indonesia’s culture itself, including intangible heritage. In addition, Another effort that can be done is to hold an art exhibition or exhibition. The results of this study indicate that the concept of "safeguarding" in the 2003 UNESCO Convention is interpreted as protection, safeguarding, preservation of an open intangible heritage. This means that a country which is not the owner of such intangible wealth is still allowed to use, display or create an object which is an inheritance of the Intangible Cultural Heritage of another country as long as the beneficiary country does not claim to be the culture of its country.